Grammatical Framework For Multilingual Natural Language Generation: The Weather Report Case - Lobanov, Gleb (My University, 2017)
The thesis presents the multilingual natural language generation effort using Grammatical Frameworks and following the Reiter and Dale’s approach. Also, it provides an outline for a type-theoretical procedure for document planning, which appears to succumb to formalization as a proof search under a linear context. To demonstrate the applicability of the method to various domains, we created a text robot, which summarizes weather data in English and Russian.
Keywords: Data- och informationsvetenskap; Computer and Information Science